INISIASI PENDAMPINGAN UKM PRODUSEN MINUMAN YOGHURT PADA KELOMPOK ‘SEHAT JIWA’ BINAAN BMH MALANG - Sri Rulianah; Dwina Moentamaria; Prayitno Prayitno (Publisher UPT P2M Politeknik Negeri Malang, 2019)
As a follow-up to the 2018 regular PkM program, where the Chemical Engineering Department has succeeded in yoghurt making training for ‘SEHAT JIWA’ group as build of BMH Malang which is shown by the increasing enthusiasm of the training participants who wish to open a business making yoghurt drinks to be marketed in the surrounding area.The purpose of this PkM is to provide technical assistance and provision of equipment for the production of yoghurt to SMEs of drink producers under the guidance of BMH of Malang in order to become independent and ready to compete in the market. This PkM activity consists of several activities, including: 1). Yoghurt production assistance, 2). Provision/grant of yoghurt production equipment (Pasteurization and incubation, Freezer).The results of the PkM show that increasing of the knowledge and skills of the participants in operating the grant equipment (pasteurization and incubation - freezer) used to make yoghurt. Besides that, increased an understanding of the introduction and application of the management of production and marketing of yogurt. Furthermore, several PkM outcomes have been achieved, including: An article published in national journals with ISSN, Publications of activities in national newspapers (on line), Patent Draft, and Equipment Grants.